Gwendy's Magic Feather - Chizmar, Richard, 1965-; King, Stephen, 1947-; Minnion, Keith (Baltimore, Maryland : Cemetery Dance Publications, 2019)
"Something evil has swept into the small western Maine town of Castle Rock on the heels of the latest winter storm. Sheriff Norris Ridgewick and his team are desperately searching for two missing girls, but time is running out to bring them home alive. In Washington D.C., thirty-seven-year-old Gwendy Peterson couldn't be more different from the self-conscious teenaged girl who once spent a summer running up Castle Rock's Suicide Stairs. That same summer, she was entrusted - or some might say cursed - with the extraordinary button box by Richard Farris, the mysterious stranger in the black suit. The seductive and powerful box offered Gwendy small gifts in exchange for its care and feeding until Farris eventually returned, promising Gwendy she'd never see the box again. One day, though, the button box shows up without warning - and without Richard Farris to explain why, or what she's supposed to do with it. The mysterious reappearance of the box, along with the troubling disappearances in Castle Rock, leads Gwendy home again... where she just might be able to help rescue the missing girls and stop a madman before he does something ghastly."--Publisher description.
"Sequel to Gwendy's button box co-written with Stephen King"--Jacket.
Keywords: Missing children -- Fiction; Magic paraphernalia -- Fiction; Castle Rock (Me. : Imaginary place) -- Fiction; Homecoming -- Fiction; Horror fiction